EVALUASI PENGGUNAAN OBAT COMMOND COLD PADA PENGOBATAN SENDIRI DI MASYARAKAT DESA KARANGGONDANG KECAMATAN MLOGO KABUPATEN JEPARA - ibrahim arifin; kristian teguh prasetyo; nanang munif yasin (Universitas Wahid Hasyim Semarang, 2009)
ABSTRACTCommon Cold is a resporatory disturbance symptom which well-marked by cough, sneez, clogged up nose,painful red lane, fever, and headache. Nowadays, people tend to have self medication to cope with Common Cold byconsuming free medicines and limited free medicines which sold freely in market. The aim in this research was toevaluate Common Cold medicines utilizat ion by people in Karanggondang Mlonggo Jepara.This research is a non-experimental study. Data was obtained from field survey by using quetionnaire thathave been filled by people in Karanggondang Mlonggo Jepara. The result in this research have being analized byusing descriptive non analytical method. Sample was taken proportionally with convenient sampling method.This research showed that description of self medicat ion on Karanggondang Mlonggo Jepara peple wassufferer frequency 40,25% then action that have been taken by Common Cold sufferer who tried to do selfmedication 77,75%, their reason to do self medication based on experience was 33%, basic of medicines choice ofself medication who fiitted in with certain medicines was 23,75%, informat ion source of respondents from books ormass media was 44,75%. The result of evaluation with Common Cold medicines utilization on KaranggondangMlonggo Jepara people showed that correct indication 80,06%, correct medicines 80,06%, correct patients 65,59%,correct dosage 72,67% and on guard of sleepy side effect which occur oftenly 35,69%.Key words : Medicines Utilization , Common Cold, Self-Medication, Karanggondang People